Effects of hydrogen-damaged layer on tin-doped indium oxide etching by H2/Ar plasma. (22nd May 2017) - Hirata, Akiko; Fukasawa, Masanaga; Shigetoshi, Takushi; Okamoto, Masaki; Nagahata, Kazunori; Li, Hu; Karahashi, Kazuhiro; Hamaguchi, Satoshi; Tatsumi, Tetsuya
Abstract: The etch rate of tin-doped indium oxide (or indium tin oxide, ITO) and the effects of a hydrogen-damaged layer caused by H2 /Ar plasma were investigated using several surface analysis techniques. The ITO etch rate strongly depended on the H2 /Ar flow rate ratio. The ITO was reduced by hydrogen injection and generated an In-rich (hydrogen-induced damage) layer on the surface. Because this In-rich layer had a higher sputtering yield, the hydrogen-damaged layer enhanced the ITO etch rate. Thus, the etching of ITO in H2 /Ar plasma is determined by the balance between the formation of the In-rich damaged layer by H ion irradiation and the sputtering by Ar (relatively heavy inert gas) ions.